Genomic sequencing combined with marker-assisted breeding effectively eliminates potential linkage drag of a target gene: a case study in tobacco - Gao, Wenxia; Yu, Wen; Lin, Jinbin; Zhao, Zhenfu; Yin, Ningning; Lai, Juxian; Cheng, Yazhi; Huang, Likun; Li, Chunying; Chen, Shunhui; Wu, Weiren; Wu, Shengxin (Frontiers in Plant Science, 2025)
Linkage drag frequently impedes the utilization of beneficial genes from wild species in crop improvement. The N gene from Nicotiana glutinosa confers strong resistance to tobacco mosaic virus (TMV) but introduces linkage drag when introgressed into cultivated tobacco (Nicotiana tabacum). To address this issue, we sequenced the TMV-resistant flue-cured tobacco line 0970A and carried out comparative genomic analysis. Additionally, we used molecular markers to screen a BC4F1 population derived from the cross between 0970A and an elite flue-cured tobacco variety CB-1 (recurrent parent). As a result of sequencing 0970A, the N gene was located at the end of chromosome Nt11. The comparative genomic analysis showed that 0970A inherited approximately 3.74 Mb of N. glutinosa DNA (N-fragment) from its donor, Coker 176. From screening the BC4F1 population with molecular markers, a recombinant was identified. This recombinant had a significantly reduced N-fragment (~270 kb), which minimized the linkage drag while still maintaining resistance to TMV. This research indicates that the combination of genome sequencing and marker-assisted breeding can be successfully applied to reduce linkage drag. The findings offer valuable resources for breeding tobacco with resistance to TMV.